The role of enhanced expression of Cx43 in patients with ulcerative colitis - Liu Weidong; Feng Yan; Li Ting; Shi Tian; Hui Wenjia; Liu Huan; Gao Feng (Open Medicine, 2024)
The pathogenesis of ulcerative colitis (UC) involves chronic inflammation of the submucosal layer and disruption of epithelial barrier function within the gastrointestinal tract. Connexin 43 (Cx43) has been implicated in the pathogenesis of intestinal inflammation and its associated carcinogenic effects. However, a comprehensive analysis of Cx43’s role in mucosal and peripheral immunity in patients with UC is lacking. In this study, the colon tissues of patients with UC exhibited severe damage to the intestinal mucosal barrier, resulting in a significant impairment of junctional communication as observed by transmission electron microscopy. The mRNA expression of Cx43 was found to be significantly elevated in the UC group compared to the control group, as determined using the Affymetrix expression profile chip and subsequently validated using qRT-PCR. The immunofluorescence analysis revealed a significantly higher mean fluorescence intensity of Cx43 in the UC group compared to the control group. Additionally, Cx43 was observed in both the cell membrane and nucleus, providing clear evidence of nuclear translocation. The proportion of Cx43 in the UC group for CD4+ and CD8+ T lymphocytes was increased in the control group, but only the proportion of Cx43 for CD8+ T lymphocytes showed significant difference by flow cytometry. The involvement of Cx43 in the pathogenesis of UC and its potential role in mucosal immunity warrants further investigation, as it holds promise as a prospective biomarker and therapeutic target for this condition. The proportion of Cx43 in the UC group for CD4+ and CD8+ T lymphocytes was increased in the control group, but only the proportion of Cx43 for CD8+ T lymphocytes showed a significant difference.